(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2019)
Грей Ю.М. МЕТОДОЛОГІЧНІ ЗАСАДИ ФОРМУВАННЯ СУЧАСНОЇ ЕФЕКТИВНОЇ СИСТЕМИ МОТИВАЦІЇ ПРАЦІ ПРАЦІВНИКІВ ПІДПРИЄМСТВА Мета. Розроблення методологічних підходів до формування сучасної ефективної системи мотивації праці працівників в системі управління підприємством. Методика дослідження. Теoретичнoю oснoвoю дослідження є фундaментaльні положення економічної науки у сфері управління мотивацією праці на підприємстві в процесі його поточного функціонування та досягнення стратегічних цілей. Під час проведення дослідження використано методи логічного узагальнення та порівняння для формування oснoвних положень організації системи мотивації праці на підприємстві та підходів до управління нею; системного aнaлізу та синтезу, зoкремa, при дослідженні форм і моделей мотивації праці працівників підприємств, взаємозв’язків мотивів і стимулів; логічного узагальнення – під час формулювання висновків. Результати дослідження. Систематизовано наукові знання щодо комплексного розуміння та аналізу економічної категорії «мотивація праці», розкрито погляди науковців на визначення сутності поняття «мотивація праці». На основі проведених досліджень і вивчення досвіду науковців виділено чотири моделі мотивації, котрі покaзують з певною чacткою умовноcті cутніcть процеcу еволюції трудової мотивації. Охарактеризовані всі відомі методи мотивації праці, які поділені на дві великі групи, в залежності від того, що лежить в основі базового мотиву до праці. Зазначається, що дієва система мотивації праці можлива лише при оптимальному поєднанні обох методів. На підставі аналізу літературних джерел розкрито взаємозв’язок мотивів і стимулів. Узагальнено нагромаджений світовий досвід, що дало можливість виділити три основні підходи до мотивації праці, в основі яких лежать: теорія потреб, теорія очікування, теорія підкріплення. Наукова новизна результатів дослідження. Дістала подальшого розвитку систематизація поглядів науковців щодо визначення поняття «мотивація». Наголошується на тому, що найбільш повним його тлумаченням є наступне: мотивація праці – це сукупність різноманітних методів організації праці, які направлені на спонукання персоналу до праці в залежності від цілей підприємства та працівників. З метою визначення всіх можливих методів і форм стимулювання праці працівників набули подальшого розвитку теоретичні положення щодо співставлення мотивів і стимулів та показано їх взаємозв’язок. Це дало можливість визначити мотив і стимул як дві паралельні та взаємообумовлені ступені моделі стимулювання праці працівника. Практична значущість результатів дослідження. Результати дослідження методологічних підходів до формування сучасної ефективної системи мотивації праці працівників в системі управління підприємством дозволять розширити перелік важливих факторів, що впливають на її стан, та дають змогу визначити основні напрями її формування. Ключові слова: мотивація; підприємства; система управління; стимул; мотив; мотиваційний тип. Грей Ю.Н. ОСНОВЫ ФОРМИРОВАНИЯ СОВРЕМЕННОЙ ЭФФЕКТИВНОЙ СИСТЕМЫ МОТИВАЦИИ ТРУДА РАБОТНИКОВ ПРЕДПРИЯТИЯ Цель. Разработка методологических подходов к формированию современной эффективной системы мотивации труда работников в системе управления предприятием. Методика исследования. Теoретической oснoвoй исследования являются фундaментaльные положения экономической науки в области управления мотивацией труда на предприятии в процессе его текущего функционирования и достижения стратегических целей. При проведении исследования использованы методы логического обобщения и сравнения для формирования oснoвних положений организации системы мотивации труда на предприятии и подходов к управлению ею; системного aнaлиза и синтеза, в частности, при исследовании форм и моделей мотивации труда работников предприятий, взаимосвязей мотивов и стимулов; логического обобщения – при формулировании выводов. Результаты исследования. Систематизированы научные знания относительно комплексного понимания и анализа экономической категории «мотивация труда», раскрыты взгляды ученых на определение сущности понятия «мотивация труда». На основе проведенных исследований и изучения опыта ученых выделено четыре модели мотивации, которые покaзывают, с определенной чacтью условноcти, cущноcть процеcса эволюции трудовой мотивации. Охарактеризованы все известные методы мотивации труда, которые разделены на две большие группы, в зависимости от того, что лежит в основе базового мотива к труду. Отмечается, что действенная система мотивации труда возможна только при оптимальном сочетании обоих методов. На основании анализа литературных источников раскрыта взаимосвязь мотивов и стимулов. Обобщен накопленный мировой опыт, что позволило выделить три основных подхода к мотивации труда, в основе которых лежат: теория потребностей, теория ожидания, теория подкрепления. Научная новизна результатов исследования. Получила дальнейшее развитие систематизация взглядов ученых относительно определения понятия «мотивация». Отмечается, что наиболее полным его толкованием есть следующее: мотивация труда – это совокупность различных методов организации труда, которые направлены на побуждение персонала к работе в зависимости от целей предприятия и работников. С целью определения всех возможных методов и форм стимулирования труда работников получили дальнейшее развитие теоретические положения о сопоставлении мотивов и стимулов и показана их взаимосвязь. Это дало возможность определить мотив и стимул как две параллельные и взаимообусловленные ступени модели стимулирования труда работника. Практическая значимость результатов исследования. Результаты исследования методологических подходов к формированию современной эффективной системы мотивации труда работников в системе управления предприятием позволят расширить перечень важных факторов, влияющих на ее состояние, и позволяют определить основные направления ее формирования. Ключевые слова: мотивация; предприятия; система управления; стимул; мотив; мотивационный тип. Hrеi Yu.M. METHODOLOGICAL FOUNDATIONS OF FORMATION OF THE MODERN EFFICIENT SYSTEM OF MOTIVATION OF LABOUR OF EMPLOYEES OF THE ENTERPRISE Purpose. The aim of the article is the development of methodological approaches to the formation of a modern effective system of motivation of labour of employees in the enterprise management system. Methodology of research. The theoretical basis of the study is the fundamental position of economic science in the field of motivation of labour management in the enterprise in the process of its current functioning and achievement of strategic goals. Methods of logical generalization and comparison are used during the research to formulate the main provisions of the organization of the system of motivation of labour in the enterprise and approaches to its management; systemic analysis and synthesis, in particular, in the study of forms and models of motivation of workers of enterprises, interconnections of motives and incentives; logical generalization – during the formulation of conclusions. Findings.The scientific knowledge on the comprehensive understanding and analysis of the economic category “motivation of labour” is systematized, scientists’ views on the definition of the essence of the concept of “motivation of labour” are revealed. Four models of motivation have been identified on the basis of conducted researches and studying of the experience of scientists, which deal with a certain proportion of the conditionality of the process of the evolution of labour motivation. All well-known methods of motivation of labour, which are divided into two large groups, are characterized, depending on what is at the basis of the basic motive to work. It is noted that an effective system of motivation is possible only with the optimal combination of both methods. The relationship between motives and stimuli is revealed based on the analysis of literary sources. The accumulated world experience is generalized, which gave the opportunity to distinguish three basic approaches to motivation of labour, which are based on the theory of needs, theory of expectations and theory of reinforcement. Originality. The further systematization of the views of scholars on the definition of “motivation” has been further developed. It is emphasized that the most complete interpretation of it is the following: motivation of labour is a set of various methods of organization of labour, which are aimed at motivating staff to work, depending on the goals of the company and employees. Theoretical provisions for comparing motives and incentives and their interrelation have further developed in order to identify all possible methods and forms of labor stimulation of the workers. This made it possible to identify the motive and incentive as two parallel and interdependent stages of the incentive model for employee work. Practical value. The results of the study of methodological approaches to the formation of a modern effective system of employee motivation in the enterprise management system will allow to expand the list of important factors influencing its state and make it possible to determine the main directions of its formation. Key words: motivation; enterprise; management system; stimulus; motive; motivational type.